Development of Soft Skills through Islamic Religious Education - Sania, Fitri; Munir, Munir; Nurlaila, Nurlaila (FKIP - Universitas Riau, 2025)
Islamic Religious Education (PAI) plays an integral role in shaping holistic character, including the development of soft skills in individuals. This article aims to examine the importance of developing soft skills through Islamic Religious Education to achieve success both personally and professionally. The research method used in this study is library research, the data sources are collected from books, website articles and previous studies. The data obtained was analyzed in depth and detail to understand the phenomenon in a broader context, as well as to draw relevant conclusions to outline the concept and application of PAI in the context of this skill development. The purpose of the study was to present a comprehensive view of how PAI can effectively play a role in training skills such as leadership, communication, and teamwork. The results show that PAI positively contributes to building characters with integrity, empathy, and responsibility, communication skills, critical thinking, and leadership, almost in all areas of study presented in the data table. The integration of PAI in the learning process can create an educational environment that encourages the development of soft skills, preparing individuals to face the complex challenges of the future.